PSYCHO-PEDAGOGICAL FEATURES OF ADAPTATION OF FIRST-YEAR STUDENTS TO STUDY IN HIGHER EDUCATIONAL INSTITUTIONS - Бондар, Людмила Вікторівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
Article is devoted to the successful adaptation of first-year students to study at a higher education institution. The significance and the role of successful adaptation in the development of students’ personality. The paper draws attention to the formation of the subject of educational activity as a condition of successful adaptation. The article defines the principles of academic disciplines for teaching first-year students: problem-based learning, individual approach to the students by the teacher control the organization of independent work of students, the use of group training forms of organization of learning activities of students